PENGARUH PENGGUNAAN MEDIA DAN PENDEKATAN PEMBELAJARAN TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA SMA NEGERI DI KABUPATEN BOGOR - Nurhayati, Neneng (Gema Widyakarya bekerjasama dengan Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2017)
terhadap hasil belajar matematika siswa.   The purpose of this study to determine the influence of learning media and learning approaches to mathematics learning outcomes. The research was done by experimental method. Large sample of 60 students, with sampling technique used is cluster sampling. Data analysis using analysis of variance (ANOVA) two lane / direction. The results of hypothesis testing obtained conclusion as follows: (1) There is a significant effect of learning media on student learning outcomes of mathematics (2) There is a significant effect of learning approaches to student learning outcomes mathematics. (3) There is a significant interaction effect between using instructional media with learning approach to student learning result of mathematics